A pa66 composition, its preparation method and use

CN122445187BActive Publication Date: 2026-10-23SHANGHAI KINGFA SCI & TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610942272.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-23
Estimated Expiration
2046-06-29

AI Technical Summary

Technical Problem

然而,该专利仅研究了增强尼龙材料,其并未涉及溴系阻燃尼龙材料的湿态电性能劣化问题

Benefits of technology

本发明通过在阻燃PA66体系中引入间规聚苯乙烯(sPS)树脂,同时通过控制溴系阻燃剂中游离溴的含量及结晶调控剂的pH值,三者协同作用,能够大幅改善溴系阻燃PA66注塑产品的湿态电性能,同时体系的力学性能满足基本要求,制备得到的PA66组合物兼具优异的湿态电性能和力学性能,在电子电气、新能源等领域有较好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a PA66 composition and a preparation method and application thereof, and comprises the following components: PA66 resin 20-45 parts, syndiotactic polystyrene 8-20 parts, glass fiber 10-50 parts, compatilizer 2-8 parts, brominated polystyrene 18-25 parts, antimony trioxide 5-8 parts, and crystallization regulator 0.1-2 parts. By introducing syndiotactic polystyrene (sPS) resin into the flame-retardant PA66 system, and by controlling the content of free bromine in the bromine flame retardant and the pH value of the crystallization regulator, the three synergistically act, so that the wet-state electrical property of the bromine flame-retardant PA66 injection-molded product can be greatly improved, meanwhile, the mechanical property of the system meets the basic requirement, and the prepared PA66 composition has excellent wet-state electrical property and mechanical property, and has a good application prospect in the fields of electronic appliances, new energy and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of engineering plastics technology, specifically relating to a PA66 composition, its preparation method, and its application. Background Technology

[0002] Flame-retardant nylon materials, with their balanced mechanical and electrical properties and stable flame retardancy, have wide applications in the electronics and electrical fields. Brominated flame-retardant nylons, due to the excellent compatibility between the flame retardant and the resin matrix, possess the best mechanical properties among flame-retardant nylons. Furthermore, because the brominated flame-retardant system primarily employs a gas-phase flame-retardant mechanism, it exhibits excellent glow wire properties, making it the preferred material for applications such as connectors in household appliances where high glow wire performance is required.

[0003] With the diversification of applications for electronic and electrical products, some products need to be used for extended periods in humid or hot and humid environments, which places clear demands on the wet-state electrical properties of materials. However, industry practice has revealed that the electrical insulation properties of brominated flame-retardant nylon decrease significantly after conditioned conditions compared to its dry state, even posing risks of breakdown and insulation failure, seriously threatening the operational safety of electronic equipment. This issue has become a key bottleneck restricting the application of brominated flame-retardant nylon in electronic and electrical products in high-humidity environments, and a technical challenge that the industry urgently needs to overcome.

[0004] Patent CN116925533B discloses a nylon composition with high CTI (Chemical Insulation Titer) and high dry and wet insulation performance, its preparation method, and applications. The core technical idea is to use a combination of chelating agents and synergists. The chelating agent complexes metal ions, reducing the destructive effect of metal ions on insulation performance, thereby improving CTI and dry and wet electrical properties under harsh conditions. However, this patent uses semi-aromatic PA6T and PA10T as resin matrices. These resins themselves have low hygroscopicity and lack universal applicability. Furthermore, the flame-retardant system in this patent is a halogen-free flame-retardant system, offering limited guidance for improving the wet electrical properties of brominated flame-retardant nylons.

[0005] Patent application CN113337110A discloses a high-flowability, high-insulation reinforced polyamide composite material and its preparation method. This method improves the insulation performance of the material by adding a certain amount of insulating masterbatch, enabling the product to maintain a high insulation level in both dry and wet conditions. However, this patent only studies reinforced nylon materials and does not address the issue of the deterioration of the wet electrical properties of brominated flame-retardant nylon materials. Summary of the Invention

[0006] To overcome the shortcomings of the prior art, the present invention aims to provide a PA66 composition that possesses both excellent wet electrical and mechanical properties.

[0007] This invention is achieved through the following technical solution: A PA66 composition, by weight, comprises the following components: 20-45 parts of PA66 resin 8-20 parts of syndiotactic polystyrene 10-50 parts glass fiber 2-8 parts compatibilizer 18-25 parts of brominated polystyrene 5-8 parts of antimony trioxide Crystallization regulator 0.1-2 parts The free bromine content in the brominated polystyrene is less than 100 ppm; the pH value of the crystallization regulator is 7.0-8.8.

[0008] This invention introduces syndiotactic polystyrene (sPS) into a PA66 matrix. Utilizing its high crystallinity, low water absorption, and non-polar inert molecular chains, it forms a uniformly dispersed hydrophobic and dense crystalline network within the continuous PA66 matrix. On one hand, this physically blocks external moisture from penetrating and diffusing into the deeper layers of the material, significantly reducing the overall moisture absorption rate. On the other hand, it forms a stable, inert coating interface on the surface of the brominated polystyrene flame-retardant particles, limiting the migration and precipitation of residual trace amounts of free bromine and small-molecule bromides, and preventing direct contact between acidic impurities and the PA66 matrix. Combined with a weakly alkaline crystallization regulator with a pH controlled between 7.0 and 8.8, a mild, neutral to weakly alkaline microenvironment is constructed within the composite system. This neutralizes trace amounts of hydrobromic acid and acidic brominated byproducts precipitated from the brominated polystyrene, eliminating the conductive and catalytic degradation effects of acidic ions. Simultaneously, the crystallization regulator also plays a role in heterogeneous nucleation, refining grains and improving crystal uniformity, further limiting the diffusion and migration of moisture and ions, and working in conjunction with sPS. The physical barrier effects complement each other, doubly enhancing wet-state insulation stability. Furthermore, controlling the free bromine content of brominated polystyrene to below 100 ppm significantly reduces the content of active elemental bromine, trace bromide ions, and acidic small-molecule impurities such as hydrogen bromide that easily precipitate during thermal processes. The synergistic effect of these three factors significantly improves the wet-state electrical properties of flame-retardant PA66 injection-molded products, while the mechanical properties of the system meet basic requirements.

[0009] In the PA66 composition of the present invention, the mass percentage of PA66 resin is not less than 15%.

[0010] Preferably, the relative viscosity of the PA66 resin is 2.0-2.8, measured using an Ubbelohde viscometer under conditions of 96% concentrated sulfuric acid and 25°C according to the ISO 307:2019 test standard.

[0011] In the PA66 composition of the present invention, the mass percentage of syndiotactic polystyrene is 5%-28% (for example, it can be 5%, 6%, 7%, 8%, 10%, 12%, 15%, 17%, 18%, 20%, 22%, 25%, 28% or any range between the above proportions).

[0012] The syndiotactic polystyrene of the present invention can be obtained commercially or prepared in-house. The preparation method is described in reference to CN112646066B.

[0013] Preferably, the syndiotactic polystyrene has a weight-average molecular weight of 0.7 × 10⁻⁶. 5 -2.4×10 5 g / mol. The test method was as follows: referring to GB / T 36214.4-2018, a high-temperature gel permeation chromatography system (GPC-IR, Polymer Char, Spain, equipped with dual infrared and viscosity detectors) was used, with 1,2,4-trichlorobenzene as the mobile phase, a flow rate of 1.0 mL / min, a column temperature of 160℃, a detector temperature of 160℃, and an injector temperature of 160℃. A calibration curve was established using polystyrene standards (weight-average molecular weight range: 266-12,900,000 g / mol). The sample was dissolved in trichlorobenzene (concentration 0.125 mg / mL), and the injection volume was 200 μL. The data were processed using GPC ONE software to obtain the weight-average molecular weight (Mw).

[0014] Preferably, the mass ratio of the syndiotactic polystyrene to PA66 resin is 1:(1-4) (for example, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4 or any range between the above ratios).

[0015] More preferably, the mass ratio of the syndiotactic polystyrene to PA66 resin is 1:(2-3).

[0016] In the PA66 composition of the present invention, the mass percentage of brominated polystyrene is 11%-35% (for example, it can be 11%, 13%, 15%, 17%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35% or any range between the above proportions).

[0017] Preferably, the free bromine content in the brominated polystyrene is less than 100 ppm, and more preferably less than 80 ppm (for example, it can be 98 ppm, 95 ppm, 90 ppm, 85 ppm, 80 ppm, 74 ppm, 70 ppm, 65 ppm, 60 ppm, 56 ppm, 50 ppm, 43 ppm, 38 ppm, 30 ppm, 24 ppm, 20 ppm, 15 ppm, 10 ppm, 5 ppm or any of the above proportions).

[0018] The free bromine content in the brominated polystyrene described in this invention can be determined by the following method: Weigh 5.000 g of the dried sample, accurate to 0.1 mg, and place it in a 250 ml beaker. Add 100 ml of tetrahydrofuran and stir magnetically for 15 min. After stirring, add 25 ml of methanol, 5 ml of pure water, 1 ml of (30%) nitric acid, and 1 ml of methyl orange solution. Immerse the electrode in the test solution and titrate with a standardized silver nitrate solution, recording the results. Each sample is measured in triplicate, and the values ​​are calculated according to the following formula. The test results are retained to two decimal places.

[0019] ; Br / ppm -- Free bromine content in the sample, unit: ppm; V0 -- The volume of silver nitrate methanol solution consumed in the blank, in ml; V EP1 --The volume of silver nitrate methanol solution consumed at the first equivalence point (jump point), in ml; C AgNO3 --Concentration of silver nitrate methanol solution, unit: mol / L; m -- Sample mass, unit: g.

[0020] Preferably, the pH value of the crystallization regulator is 7.0-8.8 (for example, it can be 7.0, 7.3, 7.5, 7.8, 8.0, 8.2, 8.4, 8.8 or any range between the above values).

[0021] The pH value of the crystallization regulator described in this invention was determined according to the ISO 10390:2021 method, and the extraction medium was water.

[0022] In the PA66 composition of the present invention, the weight fraction of the crystallization regulator is 0.1-2 parts, for example, it can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.2 parts, 1.5 parts, 1.7 parts, 1.9 parts, 2.0 parts or any range between the above values.

[0023] Preferably, the crystallization regulator is one or more of talc, titanium dioxide, and long-chain calcium carboxylate, and more preferably a compound of titanium dioxide and long-chain calcium carboxylate.

[0024] The preferred D50 particle size range of the crystallization regulator of the present invention is 0.2~10μm. The test method is to use a laser particle size analyzer to measure the particle size. The test medium is deionized water. After being fully dispersed by ultrasound, the particle size is measured by the laser particle size analyzer. The arithmetic mean of parallel tests is taken. D50 is the characteristic particle size corresponding to 50% of the cumulative volume distribution of the powder.

[0025] Preferably, the compatibilizer is maleic anhydride-grafted polyphenylene ether resin. More preferably, the maleic anhydride grafting rate of the maleic anhydride-grafted polyphenylene ether resin is between 0.2% and 1.5% (for example, it can be 0.2%, 0.4%, 0.5%, 0.7%, 0.8%, 0.9%, 1.0%, 1.2%, 1.4%, 1.5% or any of the above proportions).

[0026] The maleic anhydride-grafted polyphenylene ether resin of the present invention can be obtained commercially or by self-production. The self-production method can be as follows: PPE resin, maleic anhydride and initiator are added to a twin-screw extruder in proportion and mixed at 260~280°C to obtain maleic anhydride-grafted polyphenylene ether resins with different grafting rates.

[0027] The initiator is at least one of 1,4-di-tert-butylperoxyisopropylbenzene, diisopropylbenzene peroxide, benzoyl peroxide, and di-tert-butyl peroxide.

[0028] The maleic anhydride grafting rate test method for maleic anhydride-grafted polyphenylene ether resin (MAH-g-PPE) of the present invention adopts an acid-base titration method. Specifically, acetone is used as a solvent to remove unreacted maleic anhydride in MAH-g-PPE by Soxhlet extraction. Then, MAH-g-PPE is dissolved in an organic solvent (such as xylene). Then, an excess of strong base (such as sodium hydroxide) is added to hydrolyze the anhydride groups. Then, the unreacted strong base is back-titrated with a strong acid (such as hydrochloric acid). Finally, the maleic anhydride grafting rate of MAH-g-PPE is calculated based on the titration results.

[0029] Preferably, the glass fiber is alkali-free chopped glass fiber, and more preferably, hydrolysis-resistant alkali-free chopped glass fiber.

[0030] As a further preferred embodiment of the present invention, the glass fiber is a hydrolysis-resistant, alkali-free short-cut glass fiber with a chopped length of 3-4.5 mm and an average diameter of 9-13 mm.

[0031] Depending on actual performance requirements, the PA66 composition of the present invention may further include 0-3 parts by weight of processing aids, wherein the processing aids include at least one of lubricant and antioxidant.

[0032] Preferably, the antioxidant is at least one of hindered phenols or hindered amines.

[0033] For example, the antioxidants include, but are not limited to, antioxidant 1098, antioxidant 1010, antioxidant 1076, antioxidant 245, antioxidant 168, etc.

[0034] Preferably, the lubricant is one or more of silicone, ethylene-acrylic acid copolymer wax, or sodium lignite.

[0035] The present invention also provides a method for preparing the above-mentioned PA66 composition, comprising the following steps: According to the formula, except for the glass fiber side feed, all components are mixed evenly and fed to the main feeder. After melt blending, the mixture is extruded and granulated to obtain the flame-retardant PA66 composition.

[0036] Preferably, the melt blending is carried out in a twin-screw extruder with a length-to-diameter ratio of 36 to 48:1 (e.g., 36:1, 38:1, 40:1, 42:1, 45:1, 48:1 or any range thereof), a screw speed of 300 to 500 rpm (e.g., 300 rpm, 320 rpm, 350 rpm, 400 rpm, 430 rpm, 460 rpm, 500 rpm or any value between these ranges), and an extrusion temperature of 270 to 290°C (e.g., 270°C, 275°C, 280°C, 285°C, 290°C or any value between these ranges).

[0037] The present invention also provides a household appliance connector comprising the above-described PA66 composition.

[0038] Compared with the prior art, the present invention has the following beneficial effects: This invention introduces syndiotactic polystyrene (sPS) resin into a flame-retardant PA66 system. By controlling the content of free bromine in the brominated flame retardant and the pH value of the crystallization regulator, the three factors work synergistically to significantly improve the wet electrical properties of brominated flame-retardant PA66 injection molded products. At the same time, the mechanical properties of the system meet the basic requirements. The prepared PA66 composition has both excellent wet electrical and mechanical properties and has good application prospects in the fields of electronics, electrical engineering, and new energy. Detailed Implementation

[0039] The present invention will be further illustrated below through specific embodiments. The following embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following embodiments.

[0040] The raw materials used in this invention are sourced from the following sources: PA66-1 resin: PA66 U2501 manufactured by Invista has a relative viscosity of 2.1 at 25°C; PA66-2 resin: PA66 U4800 manufactured by Invista has a relative viscosity of 2.7 at 25°C; sPS-1 resin: weight average molecular weight is 2.02 × 10⁻⁶ 5g / mol, self-made: At a polymerization temperature of 70℃, 3.8 L of toluene, 10.0 L of styrene, 9 L of methylaluminoxane toluene solution (containing 15 mol of methylaluminoxane), and 2 L of pentamethylcyclopentadienyl-(3,5-di(trifluoromethyl)-4-quinolinoxy)-dimethoxytitanium / toluene solution (containing 10 mmol of catalyst) were added sequentially, and the timer was started. After 2 hours of polymerization, the reaction solution was carefully poured into the reactor, acidified ethanol was added, and the mixture was stirred thoroughly and filtered to obtain the polymer. The filter cake was vacuum dried and weighed to obtain the polymer. The polymer was refluxed in boiling acetone, filtered while hot to obtain the solid polymer, and then vacuum dried to obtain sPS-1. sPS-2 resin: weight average molecular weight is 0.72 × 10⁻⁶ 5 g / mol, self-made: At a polymerization temperature of 55℃, 3.8 L of toluene, 10.0 L of styrene, 9 L of methylaluminoxane-toluene solution (containing 15 mol of methylaluminoxane), and 2 L of pentamethylcyclopentadienyl-4-quinolinoxy-dimethoxytitanium / toluene solution (containing 10 mmol of catalyst) were added sequentially, and the timer was started. After 2 hours of polymerization, the reaction solution was carefully poured into a reactor, acidified ethanol was added, and the mixture was stirred thoroughly and filtered to obtain the polymer. The filter cake was vacuum dried and weighed to obtain the polymer. The polymer was refluxed in boiling acetone, filtered while hot to obtain a solid polymer, and then vacuum dried to obtain sPS-2. Compatibilizer: Self-made maleic anhydride-grafted polyphenylene ether resin with a maleic anhydride grafting rate of 0.5 wt%. Preparation method: Polyphenylene ether resin, commercially available maleic anhydride, and initiator 1,4-di-tert-butylperoxyisopropylbenzene are added to a twin-screw extruder. The feed ratio of maleic anhydride, polyphenylene ether, and initiator is controlled at 0.6:99.1:0.3 for mixing to obtain a maleic anhydride-grafted polyphenylene ether resin with a grafting rate of 0.5 wt%. The extrusion temperatures of zones 1 to 10 of the twin-screw extruder are 260℃, 260℃, 270℃, 280℃, 250℃, 250℃, 250℃, 250℃, 260℃, and 280℃, respectively.

[0041] Brominated polystyrene 1: Free bromine content 75ppm, BPS 7010, Shandong Tianyi Chemical Co., Ltd.; Brominated polystyrene 2: Free bromine content 85ppm, SR-7010, Shandong Xurui New Material Co., Ltd.; Brominated polystyrene 3: Free bromine content 158ppm, SAYTEX HP-5010PST, Albemarle Group; Antimony trioxide (antimony white): S-04N, shimmering star; Talc: HTP Ultra 5L, particle size D50 of 0.65 microns, pH value of 8.2, made by IMIFABI, Italy; Silica: SP-10, particle size D50 is 10 nanometers, pH is 5.5, Huijing Nano; Titanium dioxide: ALTIRIS 550, particle size D50 of 0.5 microns, pH 8.0, Huntsman; Long-chain calcium carboxylate: LICOMONT CAV102 PWD, with a particle size D50 of 5 micrometers after grinding and screening, and a pH value of 8.5, Clariant; Calcium carbonate: AC-05N, after screening, the particle size D50 is 3.5 micrometers, the pH value is 9.5, Guangdong Xianglong Technology; Fiberglass: ECS10-03-568H, Jushi Group; Antioxidant: RIANOX 1098, Tianjin Lialong; Lubricant: Silicone GT-300, Zhejiang Jiahua Fine Chemicals.

[0042] Preparation methods for the examples and comparative examples: According to the proportions in Table 1-2, except for the glass fiber side feed, all components were mixed evenly and fed into the main feeder, and then extruded and granulated using a twin-screw extruder. The length-to-diameter ratio of the twin-screw extruder was 40:1, the screw speed was 450 rpm, and the extrusion temperature was 270~290℃.

[0043] Performance testing standards or methods: The prepared composite material particles were dried in an oven at 120°C for 4 hours, and then injection molded into 100*100*1mm square plates and ISO178:2019 bending strips to evaluate the wet electrical and mechanical properties of the material.

[0044] Wet-state electrical performance evaluation method: The obtained square plate was placed at 85℃ and 85%RH humidity for 168h. After being taken out, the surface moisture was wiped off, and after cooling to room temperature, the insulation resistance was tested within 30min. The test conditions were 1500V DC and the test time was 60s.

[0045] Mechanical property evaluation: According to ISO 178:2019, at a speed of 2 mm / min, the deflection of the material was tested.

[0046] Table 1. Components (parts by weight) and test results in Examples 1-8

[0047] Table 2. Components (parts by weight) and test results in Comparative Examples 1-5

[0048] As can be seen from the comparison between Example 1 and Comparative Examples 1-2, when the mass ratio of sPS resin to PA66 is outside the range, the wet electrical and mechanical properties of the composition cannot be simultaneously achieved.

[0049] As can be seen from the comparison between Example 1 and Comparative Example 3, when the free bromine content in brominated polystyrene is high, the wet electrical properties of the composition decrease significantly.

[0050] As can be seen from the comparison between Example 1 and Comparative Examples 4-5, the wet electrical and mechanical properties of the composition are worse than those of Example 1 when a crystallization regulator with a pH value outside the range is selected.

Claims

1. A PA66 composition, characterized in that, By weight, it includes the following components: 20-45 parts of PA66 resin 8-20 parts of syndiotactic polystyrene 10-50 parts glass fiber 2-8 parts compatibilizer 18-25 parts of brominated polystyrene 5-8 parts of antimony trioxide Crystallization regulator 0.1-2 parts The free bromine content in the brominated polystyrene is less than 100 ppm; the pH value of the crystallization regulator is 7.5-8.8, and the crystallization regulator is one or more of talc, titanium dioxide, and long-chain calcium carboxylate. The mass ratio of the syndiotactic polystyrene to PA66 resin is 1:(1-4).

2. The PA66 composition according to claim 1, characterized in that, The weight-average molecular weight of the syndiotactic polystyrene is 0.7 × 10⁻⁶. 5 -2.4×10 5 g / mol.

3. The PA66 composition according to claim 1, characterized in that, The mass ratio of the syndiotactic polystyrene to PA66 resin is 1:(2-3).

4. The PA66 composition according to claim 1, characterized in that, The free bromine content in the brominated polystyrene is less than 80 ppm.

5. The PA66 composition according to claim 1, characterized in that, The relative viscosity of the PA66 resin is 2.0-2.8, which was measured using an Ubbelohde viscometer under 96% concentrated sulfuric acid and 25°C conditions according to the ISO 307:2019 test standard.

6. The PA66 composition according to claim 1, characterized in that, The crystallization regulator is a compound of titanium dioxide and long-chain calcium carboxylate.

7. The PA66 composition according to claim 1, characterized in that, The compatibilizer is maleic anhydride-grafted polyphenylene ether resin.

8. The PA66 composition according to claim 7, characterized in that, The maleic anhydride grafting rate of the maleic anhydride-grafted polyphenylene ether resin is between 0.2% and 1.5%.

9. The PA66 composition according to claim 1, characterized in that, The glass fiber is alkali-free short-cut glass fiber.

10. The PA66 composition according to claim 1, characterized in that, The glass fiber is a hydrolysis-resistant, alkali-free chopped glass fiber.

11. The PA66 composition according to claim 1, characterized in that, The glass fiber is a hydrolysis-resistant, alkali-free short-cut glass fiber with a chopped length of 3-4.5 mm and an average diameter of 9-13 mm.

12. The PA66 composition according to claim 1, characterized in that, The product also includes 0-3 parts by weight of processing aids, which include at least one of lubricant and antioxidant.

13. A method for preparing the PA66 composition according to any one of claims 1-12, characterized in that, The process includes the following steps: according to the formula, except for the glass fiber side feed, the components are mixed evenly and fed to the main feeder, melt-blended and then extruded and granulated to obtain the PA66 composition.

14. A household appliance connector comprising the PA66 composition according to any one of claims 1-12.

Citation Information

Patent Citations

  • A catalytic polymerization system and polymerization method for styrene polymerization and the resulting polystyrene

    CN112646066B

  • High-fluidity and high-insulation reinforced polyamide composite material and preparation method thereof

    CN113337110A

  • Flame-retardant nylon composition as well as preparation method and application thereof

    CN114196199A

  • Brominated flame-retardant polyamide composition for improving air trapping

    CN119613952A